2016
DOI: 10.1017/s0007114516000751
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian dietary patterns and the risk of breast cancer in a low-risk population

Abstract: Among cancers in American women, breast cancer (BC) has the second highest incidence and mortality. The association of BC with diet has been inconsistent. Studies that evaluate associations with dietary patterns are less common and reflect an individual's whole diet. We associated dietary patterns with the risk of BC in American women of the Adventist Health Study-2 (AHS-2), a prospective cohort of 96 001 subjects recruited between 2002 and 2007. Answers to a previously validated FFQ were used to classify subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 64 publications
4
39
0
3
Order By: Relevance
“…1). This selection process led to the consideration of nine studies (15)(16)(17)(18)(19)(20)(21)(22)(23) to be included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). This selection process led to the consideration of nine studies (15)(16)(17)(18)(19)(20)(21)(22)(23) to be included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Four datasets from four studies (17,18,21,22) were analysed to test the association of vegetarian compared to a non-vegetarian diet and breast cancer risk (Fig. 2).…”
Section: Vegetarian Diets and Breast Cancer Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…One study examined vegetarian patterns in relation to breast cancer (BC) risk using data from 96,001 adults taking part in the prospective Adventist Health Study-2 (2002–2007). Findings showed that vegans had a significantly lower risk of BC compared with vegetarian and NVs (24). …”
Section: Healthmentioning
confidence: 97%
“…Vegetarian diets were protective against gastrointestinal cancers and vegan diets were associated with lower overall cancer incidence and female-specific cancers [121]. Separate analyses of prostate, breast, and colorectal cancers showed a trend towards lower risks for Blacks, although the results were non-significant [116,117,119].…”
Section: Findings In Black Adventistsmentioning
confidence: 93%